2015
DOI: 10.1108/jrme-09-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Expressing herself through brands: the Arab woman’s perspective

Abstract: Purpose -This paper aims to extend Wallström et al.'s (2010) six-nation study on brand use and notions of self-expression to Arab women in the UAE. Additionally, it extends the scope of investigation to include an extensive qualitative data corpus to inform and explain the consumption practices of this large, very wealthy and under-researched sector of the global marketplace. Design/methodology/approach -The paper uses mixed methodology emphasizing qualitative research as a means of building on the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The selfexpressive role of brands depends also on religiosity. Alserhan et al (2015) extended Wallström et al's (2010) six-nation study to Arab women from the United Arab Emirates. The study revealed that the importance of brands as vehicles of self-expression for Arab women is the lowest, compared to other countries.…”
Section: Cultural and Economic Differences In Brandrelated Consumer Behaviourmentioning
confidence: 74%
See 2 more Smart Citations
“…The selfexpressive role of brands depends also on religiosity. Alserhan et al (2015) extended Wallström et al's (2010) six-nation study to Arab women from the United Arab Emirates. The study revealed that the importance of brands as vehicles of self-expression for Arab women is the lowest, compared to other countries.…”
Section: Cultural and Economic Differences In Brandrelated Consumer Behaviourmentioning
confidence: 74%
“…There has also been evidence showing how culture and economic factors shape the expressing of oneself through brands (Alserhan et al, 2015;Wallström et al, 2010). Not only consumers from individualistic cultures but also consumers from collectivist cultures use brands for self-expression (Aaker and Schmitt, 1997).…”
Section: Cultural and Economic Differences In Brand-related Consumer Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…developing countries or developed countries) is recommended for comprehensive understanding of country image effects. Moreover, product quality was found to be important in the purchase choices of beauty care products among Arab women (Alserhan et al , 2015) and in brand attitudes toward sunglasses among the Generation Y consumers in Iran (Esmaeilpour, 2015). Therefore, an accurate understanding of country image effects among Saudi consumers warrants investigation of product quality together with country image.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, consumers who purchase luxury apparel are highly involved in fashion (O'Cass, 2004). This suggests that what the consumers deem fashionable will directly impact their attitudes, which are often socially motivated (Alserhan et al, 2015). Hence, the more consumers perceive the luxury apparel brand as being socially acceptable and trendy, the more positive their attitudes will be (Celik & Kocaman, 2017; Kim et al, 2012; O'Cass, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%